2003
DOI: 10.1046/j.1365-3180.2003.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Cynodon dactylon from stolon and rhizome fragments

Abstract: A field survey and two field experiments were carried out to compare the performance of rhizomes and stolons of Cynodon dactylon, in terms of their sprouting efficiency and the dynamics and growth characteristics of the established ramets. The survey examined the relationships between morphological characteristics of aboveand below-ground structures of ramets naturally established from both types of fragments in a crop field. The first experiment compared the emergence and early growth of ramets from standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…After establishment, managing grazing to maintain NWSG productivity could help limit bermudagrass spread. In addition, our results have implications for other types of management used to maintain NWSG stands such as disking (Harper et al ) because bermudagrass may spread by fragmentation (Fernandez ). The potential for management to affect stand composition through exotic grass invasion following NWSG establishment should therefore be carefully considered by producers and conservationists seeking to reintroduce native grasses to working landscapes.…”
Section: Discussionmentioning
confidence: 80%
“…After establishment, managing grazing to maintain NWSG productivity could help limit bermudagrass spread. In addition, our results have implications for other types of management used to maintain NWSG stands such as disking (Harper et al ) because bermudagrass may spread by fragmentation (Fernandez ). The potential for management to affect stand composition through exotic grass invasion following NWSG establishment should therefore be carefully considered by producers and conservationists seeking to reintroduce native grasses to working landscapes.…”
Section: Discussionmentioning
confidence: 80%
“…Fernandez (2003) reported emergence after about 13 d and Montesbravo et al (1985) observed the highest emergence occurred 16 to 30 DAP. In 2011, shoots started emerging at 5 DAP, and at 19 DAP partially buried stolons had a greater number of shoots than totally buried ones (3.5 vs. 7.8 shoots m -2 ).…”
Section: Shoot Emergencementioning
confidence: 95%
“…Owen and Maynard (2007) suggested that larger stems are likely to root better because of increased carbohydrate reserves. Although stolon fragments have sometimes been planted, delayed emergence, lower establishment, and a reduction in total plant dry weight have been reported when using small stolon fragments compared with intact stolons of Cynodon dactylon (Fernandez, 2003). Additionally, it has been reported that starch reserves are lower in less mature tissue at the top of the stolons than in middle and basal nodes (Volterrani et al, 2012).…”
mentioning
confidence: 99%
“…Fernandez (2003) reported bermudagrass emergence as soon as 11 DAP when using rhizome fragments. First shoots started emerging earlier than 30 DAP.…”
Section: Emergencementioning
confidence: 99%